UPAYA GURU DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA MENULIS PERMULAAN SISWA KELAS I MI - Herisfani Fauziah (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
The purpose of this reaserch is to find out how the teacher's efforts in developing beginning reading and writing skill of first grade students. This study also aims to determine what obstacles faced by teachers in developing beginning reading and writing skill of first grade students. The method used in this research is descriptive qualitative research method where data collection using interview technique, observation and documentation. In this study the authors interviewed several sources including: the headmaster of MI Nurul Falah Suradita and two teachers of MI Nurul Falah Suradita. The result of the research shows that the teacher's effort in developing beginning reading and writing skill in the first class is by giving additional tutorial, giving the reading book, using the study time well, dictating the students, using Spell reading method and reading fluently, giving motivation, giving reward, giving guidance and supervision, bringing to the library and assessing. And the obstacles of teachers in developing beginning reading and writing skill are less conducive learning and limited textbooks.